The relationship between children’s blood pressure and blood pressure of their parents - Desy Aswira Nasution; Rusdidjas dr; Supriatmo dr; Rafita Ramayati; Oke Rina Ramayani; Rosmayanti Siregar (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Background : Family history of hypertension is a risk factor for hypertension in children. Some studies have reported significant relationship of elevated blood pressure in children with hypertensive parents.Objective : To determine the relationship between blood pressure in children and blood pressure of their parents Methods : A cross sectional study was conducted in 90 children aged 6 until 18 years in Baringin village, Panyabungan on May until June 2010. Sample was collected with consecutive sampling. Classification of hypertension determined by measurement of blood pressure, height, weight based on Fourth Task Force. We used student t-test to analyzed numerical data. Simple linier regression was used to investigate the relationship between blood pressure of children and blood pressure of their parents. Results : Of 90 participants that had been examined, 24 boys and 17 girls have hypertensive parents. The mean systolic (SBP), diastolic (DBP) and mean arterial blood pressure (MABP) was significantly higher in children with hypertensive parents than normotensive parents (116.7 and 7.07 respectively ; P = 0.0001 for SBP, 77.8 and 8.33 respectively; P = 0.0001 for DBP, 90.7 and 7.41 respectively; P = 0.0001 for MABP). There was a significant relationship between elevated SBP in boys and SBP of his father was indicated by the correlation coefficient (r = 0.806; P = 0.0001).Conclusions: The blood pressure of children was significantly higher in children with hypertensive parents than normotensive parents. There was a strong correlation between SBP in boys with SBP of his father.Keywords : hypertension; blood pressure; parents; children